Casarett and Doull's toxicology : the basic science of poisons - Klaassen, Curtis D. (New York : McGraw-Hill Education, 2013)
This new seventh edition features is updated throughout and includes many new contributors and new content on chemical terrorism. Combined with the latest thinking by the field's foremost scholars plus solid coverage of general principles, modes of action, and chemical-specific toxicity, this landmark text continues to set the standard for toxicology references. An all-in-one overview of the biomedical and environmental aspects of toxicology. For Pharmacologists (20,000), pharmacists (175,000), pharmacy students (35,000), toxicology /poison control centers (5,000), pharmacology and toxicology graduate students (3000). NEW full-color design. NEW DVD with all images and tables from the text.
History and scope of toxicology -- Principles of toxicology -- Mechanisms of toxicity -- Risk assessment -- Absorption, distribution, and excretion of toxicants -- Biotransformation of xenobiotics -- Toxicokinetics -- Chemical carcinogenesis -- Genetic toxicology -- Developmental toxicology -- Toxic responses of the blood -- Toxic responses of the immune system -- Toxic responses of the liver -- Toxic responses of the kidney -- Toxic responses of the respiratory system -- Toxic responses of the nervous system -- Toxic responses of the ocular and visual system -- Toxic responses of the heart and vascular system -- Toxic responses of the skin -- Toxic responses of the reproductive system -- Toxic responses of the endocrine system -- Toxic effects of pesticides -- Toxic effects of metals -- Toxic effects of solvents and vapors -- Toxic effects of radiation and radioactive materials -- Toxic effects of plants and animals -- Toxic effects of calories -- Nanotoxicology -- Air pollution -- Ecotoxicology -- Food toxicology -- Analytical and forensic toxicology -- Clinical toxicology -- Occupational toxicology -- Regulatory toxicology.
Includes bibliographical references and index.
Keywords: TOXICOLOGY; POISONS